2014
DOI: 10.1186/1471-2458-14-687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AFP surveillance indicators in polio-free Ghana, 2009–2013

Abstract: BackgroundGhana recorded the last case of indigenous wild poliovirus in 1999 but suffered two more outbreaks in 2003 and 2008. Following the World Health Organization (WHO) guidelines, transmission was interrupted through high routine immunisation coverage with live-attenuated oral polio vaccine (OPV), effective acute flaccid paralysis (AFP) surveillance and supplementary immunisation activities (SIA). This article describes the results of a five-year surveillance of AFP in polio-free Ghana, evaluate the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 10 publications
17
36
1
Order By: Relevance
“…This study has found higher incidence of AFP among boys than in girls, 59.22% and 40.78% respectively though it is not statistically significant (p= 0.992). The similar findings of higher incidence of AFP among boys than in girls were observed in other studies as well [22,24].…”
Section: Discussionsupporting
confidence: 79%
“…This study has found higher incidence of AFP among boys than in girls, 59.22% and 40.78% respectively though it is not statistically significant (p= 0.992). The similar findings of higher incidence of AFP among boys than in girls were observed in other studies as well [22,24].…”
Section: Discussionsupporting
confidence: 79%
“…4% in Ghana and 67.2% in South Africa. 14,15 Regarding the incidence of AFP by gender, we observed similar distribution with 55% and 45% for male and female, respectively. Our results are very similar to studies performed in other areas such as Ghana, 55.8%, South Africa 54.3% for male.…”
Section: Non-polio Isolation Ratesupporting
confidence: 54%
“…Our results are very similar to studies performed in other areas such as Ghana, 55.8%, South Africa 54.3% for male. 14,15 The temperature in which the fecal samples were received at the laboratory was another important indicator analyzed. In recent study, Walker and coworkers demonstrated the effect of transport temperature on the viability of poliovirus in stool specimens suggesting that this point is important to be analyzed in tropical regions.…”
Section: Non-polio Isolation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Looking at Ghana, a country neighbouring Nigeria, which has cultural similarities, the last case of indigenous wild poliovirus was recorded in 1999; still, the country had two more outbreaks in 2003 and 2008. The result of these two outbreaks made the government double its effort to interrupt the virus through adherence to high routine immunization coverage with liveattenuated oral polio vaccine, improved AFP surveillance and supplementary immunization activities [2].…”
Section: Introductionmentioning
confidence: 99%